CONVERSATIONAL IMPLICATURE IN IN THE HEART OF THE SEA MOVIE - Yudith Yudith; M. Natsir; Indah Sari Lubis (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This research aims to find out the types and the purposes of conversational implicature uttered by all characters in In The Heart of The Sea movie by using pragmatics approach. The design of this research is qualitative research employing content analysis approach that focused on textual investigation. The data of this research is utterances, which contains conversational implicature spoken by the characters in that movie. This research has one data source which is the movie script of In The Heart of The Sea movie. The data of this research are categorized as types of conversational implicature are analyzed based on Grice’s theory (1975) and the purposes of conversational implicature used theory by Brown and Levinson (1978). The result of this research shows that two types of conversational implicature are found in the utterances of the characters in that movie, they are particularized conversational implicature and generalized conversational implicature. Five purposes of conversational implicature also found in this research, they are to protect speaker itself, to show power and politeness, to give information, to entertain the audiences (humorous) and to have lack specific information.